Psychological Well-Being, Knowledge Management Behavior and Performance: The Moderating Role of Leader-Member Exchange - Kim, Cheol Young (Frontiers in Psychology, 2021)
Knowledge is considered an essential resource and key to competitiveness. The behavior of sharing knowledge is an essential activity for the prosperity of the organization. For individuals, however, sharing knowledge can present a dilemma by giving up the exclusive right to certain knowledge that they own. This study identifies the psychological well-being as a leading factor in facilitating knowledge-sharing in dilemma situations. The author classified knowledge management behavior into sharing, hiding, and manipulating behavior, and studied them as mediators linking psychological well-being and performance. And to check the influence of the quality of the exchange relationship, leader-member exchange was used as a moderator. For the empirical analysis, 333 members from 12 organizations were surveyed by using different sources and times. Hierarchical regression analysis and bootstrapping analysis were conducted for verification of hypothesis. Results demonstrated that the psychological well-being influence directly on knowledge-sharing, -hiding, and -manipulating behaviors and indirectly on performance. In the multi-mediation test, only knowledge-sharing behavior mediated the relationship between psychological well-being and performance. And the moderating effect of leader-member exchange was significant only in the relationship between psychological well-being and knowledge-sharing behavior. This study contributes to the performance, knowledge management and positive psychology research fields, and suggests practical implications.